COMMON CULTURAL COMPETENCE AS A FACTOR OF PROFESSIONAL SUCCESS - Natalya A. Orekhovskaya (Высшее образование в России)
The empirical basis of article is provided by the results of the sociological surveyof first-year students of MGTU of N.E. Bauman, conducted by the Prof. Orekhovska N.A. and Assoc. Prof. Gavrilina E.A. The results of the students’ survey show a very low level of culture and general outlook. The authors substantiate the need for formation of students’ common cultural competences. It is necessary for their further successful selfGrealization in any professional activity including, engineering and administrative.